Two-photon circular dichroism in the algebraic diagrammatic construction framework - Papapostolou, Antonia; Schneider, Friederike; Rehn, Dirk R.; Dreuw, Andreas (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2025)
We present the calculation of the rotatory strengths of two-photon circular dichroism (TPCD) in the framework of algebraic diagrammatic construction (ADC) using the intermediate state representation (ISR). First, the differences between the length-gauge formulation of TPCD and three gauge-origin invariant approaches are investigated depending on the order of perturbation theory and the basis set. Subsequently, our ADC/ISR results are compared with results of corresponding coupled cluster methods from the literature. The calculations were performed with the recently published Python package responsefun and show that the user can calculate arbitrary sum-over-states expressions without requiring knowledge of ADC theory. The treatment of response properties with the ADC/ISR approach is computationally feasible up to the third order of perturbation theory, and thus this methodology represents a valuable addition to highly accurate ab initio benchmark methods.
Online veröffentlicht: 27. Juni 2025
Gesehen am 30.10.2025